Determinants Increasing Supervisory Effectiveness in Implementing Supply chain management and Cooperative Oversight Techniques - Made Marsa Arsana; Ketut Arya Bayu Wicaksana; Nyoman Sugiarta; Ni Luh Gede Mahayu Dicriyani (International Journal of Supply Chain Management, 2020)
Abstract— The research objective is to identify the determinants of increasing the effectiveness of intern supervisors in implementing Cooperative supply chain and supervision techniques. Research methods, data collection techniques: interviews, questionnaires and observations. Data Analysis, qualitative data is transformed into quantitative data in the form of scale. Each variable is made into five categories based on a Likert scale. The average score scale used is a scale of five namely Strongly Disagree value weighting 1, Disagree weighting value 2, Enough weighting value 3, Agree weighting value 4, Strongly agree weighting value 5. Cooperative supervisor (Y) as a dependent variable: implementation of effective supervision supply chain management (Y1) and effective supervision techniques (Y2), while the independent variables: intern factors (F1) and extern factors (F2) of the cooperative's intern supervisors. Data were analyzed with the Structural Equation Model to find intern and extern factors of cooperative supervisors as a determinant of supervisor effectiveness. The finding of the research is the effectiveness of the cooperative's intern supervisors is determined by intern factors and the cooperative supervisor's extern factors, so that in the future it is necessary to carry out these factors.